The Risks of Digital Marketing in Indonesia: A Bibliometric Analysis - Yartono , Nungki; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Digital marketing uses digital technology in the business world. The use of digital technology in marketing is also considered more advanced when compared to conventional marketing, so that 63.52% of digital users utilize digital technology for marketing. However, on the other hand, digital technology increases security risks. Therefore, an in-depth study of the risks of digital marketing in Indonesia is needed. The method used is bibliometric analysis with clustering and density models. The data needed comes from scientific literature which is available from crossref. The tools used for analysis consist of perish or publish and VOSviewer. Based on bibliometric analysis with a network visualization model, there are five keyword clusters that frequently appear, the first cluster is shown in red, which contains 10 keywords. The second cluster, shown in green, contains 10 keywords. The third cluster shown in blue contains 6 keywords. The fourth cluster shown in yellow contains 5 keywords. The fifth cluster shown in purple contains 2 keywords. Based on density analysis, the topics often discussed in studies of the determinants of e-commerce development consist of 30 words with the main word being digital marketing.